Understanding Fourth-Grade Student Achievement Using Process Data from Student’s Web-Based/Online Math Homework Exercises - Oksana Ilina; Sona Antonyan; Maria Kosogorova; Anna Mirny; Jenya Brodskaia; Manasi Singhal; Pavel Belakurski; Shreya Iyer; Brandon Ni; Ranai Shah; Milind Sharma; Larry Ludlow (Education Sciences)
Understanding how students’ online homework behaviors relate to their academic success is increasingly important, especially in elementary education where such research is still emerging. In this study, we examined three years of online homework data from fourth-grade students enrolled in an after-school math program. Our goal was to see whether certain behaviors—like how soon students started their homework, how many times they tried to solve problems, or whether they uploaded their written work—could help explain differences in homework completion and test performance. We used multiple regression analyses and found that some habits, such as beginning homework soon after class and regularly attending lessons, were consistently linked to better homework scores across all curriculum levels. Test performance, however, was harder to predict and showed fewer consistent patterns. These findings suggest that teaching and encouraging specific online study behaviors may help support younger students’ academic growth in digital learning environments.